La fábula una estrategia didáctica para la mediación del conflicto escolar (2019)
In this research project the fable is proposed as a didactic strategy to promote the mediation of the school conflict, seeking to strengthen both the personal and social training of the students; through the teaching of fables as an intervention strategy for coexistence and with the aim of improving interpersonal relationships, giving students the opportunity to reach values such as self-esteem and decision-making skills, values that help them improve relations with their peers and that in this way they can face the conflict in a positive way, generating in them processes of reflection, self-control and healthy coexistence in their environment. Hence, the fables that were carried out involved conflict mediation processes in which strategies based on assertive communication, dialogue and conciliation were given, The research approach we use is the mixed, action research, with a finite, longitudinal population, made up of the students of 4th Grade of Primary Basic Education of the I.E.T.I. José Catillo Bolívar. For which we use the following data collection instruments: participant observation, surveys, workshops, talks; seeking to improve and strengthen school life. The strategies and didactics put into practice sought to create strong bonds of friendship between the students and started from the fun of learning, the construction of fables, group and personal narratives with the interest of generating spaces for reflection, participation and expression, strengthening coexistence and teaching process - learning.